Review on Multi-Domain Interoperability in IoT Gateways: A Cross-Platform Approach to Web and Software Integration for Smart Ecosystems (International Journal of Scientific Research and Management (IJSRM), 2024)
Emphasising the integration of web and software platforms inside smart ecosystems, this review investigates the difficulties and solutions related with multi-domain interoperability in IoT gateways. Effective smart ecosystem management depends on smooth communication and data exchange between heterogeneous systems like IoT devices spread throughout many different fields. The study notes main obstacles that impede seamless integration: protocol incompatibility, security concerns, and scale problems. We discuss in great depth middleware channels, blockchain for more security, MQTT, CoAP, & common standards (e.g.). Furthermore noted is how fog computing and the edge might help to tackle bandwidth and latency issues. By means of present strategies and future approaches, this analysis emphasises the need of ongoing growth of standards and technology guaranteeing scalable, safe, and productive interoperability across numerous IoT sectors. The supplied information provides a foundation for increasing IoT system utilisation in ever more complex environments.